Preliminary study for lipid extraction from fungi biomass of Aspergillus oryzae - Hazmi, Alia Tasnim; Ahmad, Farah; Athoillah, Ahdyat Zain; Jameel, Ahmad Tariq (Kulliyyah of Engineering, International Islamic University Malaysia, 2018)
In the research of microbial biodiesel, there are numerous studies on biodiesel derived from microalgal lipids. Apart from the microalgae, biodiesel can also be produced using others oleaginous microorganisms such as yeast and fungi. There are studies that showed that oleaginous yeasts and fungi are able to accumulate lipids that can also be used as the feedstock for biodiesel production. However, there are gaps in the matter concerning biodiesel production from lipids of filamentous fungi, as well as the methods for lipids extraction from filamentous fungi. The aim of this study is to investigate the effect of different methods used during extraction on the yield of lipid and subsequently biodiesel. In this study, Aspergillus oryzae fungus was chosen as the interest strain due to its high lipid accumulation. After harvesting fungal biomass from the lipid cultivation, the biomass underwent two methods of extraction which are Bligh and Dyer method and the well-established Soxhlet method. Different solvents were used in this study, which were the mixture of chloroform and methanol for Bligh and Dyer method while hexane for Soxhlet extraction. The study showed that Bligh and Dyer method resulted in higher lipid yield in comparison to Soxhlet method. The lipids extracted can be further converted into fatty acid methyl ester (i.e. biodiesel) via transesterification.